GEOMAGNETIC FIELD OF UKRAINE: ESTIMATION OF INTERNAL AND EXTERNAL SOURCES CONTRIBUTION - Orliuk, M. I.; Romenets, A. A.; Sumaruk, T. P.; Sumaruk, Yu. P. (Одеські астрономічні публікації, 2012)
This article is considering some aspects of differentiation between internal and external sources of the Earth's magnetic field; it estimates also the contribution of different sources into total field as well as its variations. The surveys results of ukrainian magnetic observatories were used to fulfil the task.